PEMOGRAMAN ANALISIS RASIO TULANGAN BALOK BERPENAMPANG PERSEGI - Yuda Hadimas; Masril Masril; Elfania Bastian (Ensiklopedia Social Review, 2022)
Calculation of the ratio of reinforcement in reinforced concrete beams is very significant because the correct calculation of reinforced concrete beams will make the beam better and more efficient. This calculation requires a lot of time and high accuracy, so manual calculations are not efficient. Computer programming is widely developed in civil engineering calculations, for example visual basic applications. The visual basic 6.0 application used in this task is designed to make it easier for planners to calculate the reinforcement ratio in the beam accurately and quickly. Here the author explains how the process required to input data in this program. The use of formulas in the Indonesian National Standard Regulations and other applicable regulations. Then the results obtained are more accurate, the final result of this program or the output in the form of a general data comparison Calculation of the beam reinforcement ratio to be inputted in visual basic 6.0 programming requires the ultimate load (Mu) which is used to find Rn and Equivalent. When you have got what you need, you will be able to look for As necessary to continue the next search until you get the results of the required amount of reinforcement. Reinforcement Spacing ControlKeywords: Visual Basic 6.0, Beam Reinforcement Ratio